2013
DOI: 10.1063/1.4832555
|View full text |Cite
|
Sign up to set email alerts
|

Universal conductance fluctuations in electrolyte-gated SrTiO3 nanostructures

Abstract: We report low-temperature magnetoconductance measurements of a patterned two-dimensional electron system (2DES) at the surface of strontium titanate, gated by an ionic liquid electrolyte. We observe universal conductance fluctuations, a signature of phase-coherent transport in mesoscopic devices. From the universal conductance fluctuations we extract an electron dephasing rate linear in temperature, characteristic of electron-electron interaction in a disordered conductor. Furthermore, the dephasing rate has a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…The reported dephasing length are around ~100 300 nm at low temperature [512,513]. Note that the extrapolated dephasing rate does not vanish at 0 K for both reports [512,513]. Stanwyck et al [513]suggested that Kondo scattering may occur, though a Kondo resistance minimum is not reported.…”
Section: Universal Conductance Fluctuationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The reported dephasing length are around ~100 300 nm at low temperature [512,513]. Note that the extrapolated dephasing rate does not vanish at 0 K for both reports [512,513]. Stanwyck et al [513]suggested that Kondo scattering may occur, though a Kondo resistance minimum is not reported.…”
Section: Universal Conductance Fluctuationsmentioning
confidence: 95%
“…Note that the extrapolated dephasing rate does not vanish at 0 K for both reports [512,513]. Stanwyck et al [513]suggested that Kondo scattering may occur, though a Kondo resistance minimum is not reported. UCF is also reported for the superconducting critical current of a Josephson junction created from LaAlO 3 /SrTiO 3 [514].…”
Section: Universal Conductance Fluctuationsmentioning
confidence: 95%
“…It is also noteworthy that the phase coherence length in this sample is 260 nm at 1.8 K, which increases to 460 nm at 1.8 K with increasing carrier density (n 3D = 5.5 × 10 19 cm -3 ) (see figure S1). Significantly, this value is twice as large as the largest value reported for the doped SrTiO 3 at similar temperatures 32,33 indicating potential applications of doped SSO films in quantum coherent devices. We also calculated the electronelectron interaction characteristic length l ee , using ee 2 B D l k T π = h , where D is the diffusion constant of electrons 29 (see SI).…”
mentioning
confidence: 66%
“…[40][41][42][43] As shown in the figures, the magnetofingerprint is fairly retraceable on the timescale of tens of minutes, but time-varying disorder (due to the presumed two-level fluctuators responsible for the voltage fluctuations) scrambles the MR on the time scale of hours.…”
Section: Resultsmentioning
confidence: 92%